2018
DOI: 10.21470/1678-9741-2017-0184
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Risk Factors Among Dialytic Acute Kidney Injury Patients After Cardiovascular Surgery

Abstract: ObjectiveAcute kidney injury (AKI) is a frequent postoperative complication after cardiovascular surgery. It has been described as a predictor of decreased survival rates, but how dialysis decreases survival when initiated on the postoperative period has yet to be determined. To analyze the survival of patients who presented postoperative AKI requiring dialysis up to 30 days after cardiovascular surgery and its risk factors is the aim of this study. MethodsOf the 5,189 cardiovascular surgeries performed in a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
4
0
2
Order By: Relevance
“…Glomerular filtration rate (GFR) is an important component that determines the occurrence of AKI in post cardiovascular patients. Research has shown that GFR <30 before surgery is a risk factor for postoperative AKI (Silva et al, 2018). his is consistent with other studies which state that preoperative GFR can be used to predict the risk of postoperative AKI (Wu et al, 2019).…”
Section: Introductionsupporting
confidence: 86%
“…Glomerular filtration rate (GFR) is an important component that determines the occurrence of AKI in post cardiovascular patients. Research has shown that GFR <30 before surgery is a risk factor for postoperative AKI (Silva et al, 2018). his is consistent with other studies which state that preoperative GFR can be used to predict the risk of postoperative AKI (Wu et al, 2019).…”
Section: Introductionsupporting
confidence: 86%
“…It has been shown that the mortality was 50% in the patients who needed dialysis [60] . Silva et al [61] proved in a retrospective study that AKI patients requiring dialysis during postoperative period were a risk factor of late mortality. Zheng et al [9] reported that patients with oliguresis of 3 hours showed a higher drug cure rate and a lower mortality rate than those with oliguresis >5-6 hours (drug cure rate: 75.8% vs .…”
Section: Treatmentmentioning
confidence: 99%
“…Postoperative acute kidney injury (AKI), a common complication of cardiac surgery [ 7 ], is a clinical syndrome characterized by water, electrolyte, and acid-base imbalances, and accumulation of nitrogenous wastes caused by a rapid decrease in glomerular filtration function within hours to weeks [ 8 ]. AKI occurs in 2.7–70% of patients with CHD who undergo cardiac surgery [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%